Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.2105/ajph.2013.301774
|View full text |Cite
|
Sign up to set email alerts
|

The Home Foreclosure Crisis and Rising Suicide Rates, 2005 to 2010

Abstract: The foreclosure crisis has likely contributed to increased suicides, independent of other economic factors associated with the recession. Rising foreclosure rates may be partially responsible for the recent uptick in suicide among middle-aged adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 34 publications
4
82
0
1
Order By: Relevance
“…In line with previous evidence on unemployment levels and suicide [13], excess suicide deaths during the Recession have been concentrated among working-aged men [61, 63, 70, 72], who may more frequently encounter job loss and foreclosure, although the literature lacked individual-level analyses. Again, active labor market programs and social insurance appear to have substantially reduced the negative effect of unemployment on suicide rates [61, 69, 73].…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…In line with previous evidence on unemployment levels and suicide [13], excess suicide deaths during the Recession have been concentrated among working-aged men [61, 63, 70, 72], who may more frequently encounter job loss and foreclosure, although the literature lacked individual-level analyses. Again, active labor market programs and social insurance appear to have substantially reduced the negative effect of unemployment on suicide rates [61, 69, 73].…”
Section: Resultsmentioning
confidence: 76%
“…The most methodologically rigorous studies in this literature (i.e., those that use decomposition techniques and/or comparison populations) concluded that rising unemployment levels were likely to be a causal determinant of many, but by no means all, excess suicide deaths observed worldwide during the Recession [6163, 6770]. At least in the U.S., foreclosure and other housing-related distress accounted for a portion of the remaining increase in suicide rates, over and above the effect of unemployment [67, 71, 72]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A qualitative study in five US cities, which included 14 focus groups of low- and mid-income homeowners facing foreclosure as well as foreclosure avoidance professionals, identified housing payment difficulties as a major trigger of psychological feelings of insecurity and worse mental health (Libman, Fields, & Saegert, 2012). Evidence from the US also suggests that foreclosure and eviction during the housing crisis was associated with increased suicide rates (Fowler et al, 2015, Houle and Light, 2014). …”
Section: Introductionmentioning
confidence: 99%